Pengaruh Keterampilan Pemberian Penguatan Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SMAN 1 Sitiung - Edmily Wensi; Supriadi Supriadi; Afrinaldi Afrinaldi; Januar Januar (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This research is motivated by the fact that there are still many cases or problems, namely the teacher does not appreciate students who have expressed their opinions so that these students lack confidence and enthusiasm in the learning process. This research is a correlational research with a tendency of quantitative data. The sample of this study was students of class X IPA SMA N 1 Sitiung, totaling 36 people, while the sampling technique used was random sampling. Before testing the hypothesis, the researcher first conducted a prerequisite test in the form of a normality test and homogeneity test. To then proceed to test the hypothesis using a simple linear regression test. From the results of this study, it shows the analysis and discussion of the research data from the results of testing the hypothesis from the coefficients table, the sig value is obtained. equal to 0.000 <0.05, so it can be concluded that the reinforcement skill variable (X) influences learning motivation (Y). it is known that t_count is 6.111 > t_table 2.035 so that it can be concluded that the variable of reinforcement skills (X) has a positive and significant effect on the variable of student learning motivation at SMA N 1 Sitiung by 52.3%. so it can be categorized as low